Assessment of occupational exposure and spectrum of contact sensitization in metalworkers with occupational dermatitis: results of a cohort study within the OCCUDERM project. (19th January 2020) - Schubert, S.; Brans, R.; Reich, A.; Hansen, A.; Buhl, T.; Skudlik, C.; Mempel, M.; Schön, M.P.; John, S.M.; Geier, J.
Abstract: Background: Metalworkers occupationally exposed to metals, tools, metalworking fluids (MWFs), technical oils, gloves, skin care products etc. frequently suffer from occupational dermatitis (OD). Objectives: To investigate occupational exposure and to identify relevant occupational sensitizers in metalworkers with OD, and to evaluate suitability of current German patch test recommendations for this occupational group. Patients and methods: As part of the OCCUDERM project, occupational exposure of 230 metalworkers with suspected OD patch tested in the departments of dermatology in Göttingen and Osnabrück (both Lower Saxony, Germany) in 2012–2017 was recorded by questionnaire. These data, as well as results, of patch testing with standardized allergens and with workplace material were analysed. Results: Metalworking fluids and skin care products were the most important exposures. Among MWF allergens, most frequently sensitizations to formaldehyde and formaldehyde releasers, colophony/abietic acid and monoethanolamine were observed. Sensitization to methylisothiazolinone (MI) was frequent, probably as part of the general European epidemic of contact allergy to MI in leave‐on cosmetics. Sensitization to glove ingredients only played a minor role. Conclusions: The known occupational allergen spectrum could largely be confirmed. In order not to miss relevant sensitizations, patch testing with material from the patients' workplaces in parallel to baseline and MWF series is recommended. Sensitizations diagnosed could not always be linked to particular occupational exposures.